2012
DOI: 10.4172/2167-1079.1000123
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Performance of the Consumer Assessment of Healthcare Providers and Systems (CAHPS)4.0 Adult Health Plan Survey

Abstract: Background: The Consumer Assessment of Healthcare Providers and Systems (CAHPS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…[7][8][9] The survey also includes a single item asking respondents to provide an overall rating of their provider on a 0-10 scale ( Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…[7][8][9] The survey also includes a single item asking respondents to provide an overall rating of their provider on a 0-10 scale ( Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…Chong analyzed CAHPS data from Iowa and found that timeliness of care and short in-office waiting time was of greater importance to adults, while courtesy and helpfulness of office staff members was of greater importance in parental assessments of the child’s doctor. 9 Although an existing study reported similar CAHPS scores and plan rankings for adult and pediatric care, these scores can and do differ by specific components – for example, adult care was rated higher than pediatric care for customer service. 10 Information on health care experiences for both adult and pediatric care can help purchasers, health plans, and providers deliver care that fits patient’s needs.…”
Section: Introductionmentioning
confidence: 98%
“…19 Conducted quarterly since 1995, the survey utilizes protocols modeled from the Consumer Assessment of Healthcare Providers and Systems (CAHPS) survey, which is employed extensively in the civilian sector to gauge consumer opinions of health care. 20 HCSDB results are then compared to CAHPS benchmark data. Viewing data for active duty dependents from 2005 to 2014, military patient satisfaction is significantly lower than civilian satisfaction for all but two of the 11 categories, healthy behaviors (e.g., nonsmoking rate), and health plan (e.g., TRICARE).…”
Section: Introductionmentioning
confidence: 99%